Doenças de Veiculação Hídrica em Trechos da Bacia do Rio Piranhas-Assu: ocorrência de bactérias oportunistas, caracterização epidemiológica e concepções de professores e agentes de saúde - Nascimento, Viviane Silva Félix (2012)
Water is essential to life and all living organisms and their supply is necessary for economic development and quality of life of human populations, but their quality has been altered by human actions. In semi-arid northeast, the water is an issue of concern, especially its quality. This region is common to the construction of reservoirs that capture rain water, streams and temporary rivers in search of ease this situation, being intended for various purposes. Water scarcity is a limiting factor for the economic and social development of the region and contributes to the maintenance of waterborne diseases. About 80% of diseases that occur in developing countries are infected by waterborne pathogens. Therefore, this study aimed to determine in two environments that are part of semilênticos Armando Ribeiro Gonçalves reservoir, and a stretch of the river Assu, all located in the semiarid RN, the occurrence of opportunistic pathogenic bacteria; check the conceptions of teachers and health workers about the issues "waterborne diseases" and "bacteria" and a diagnosis of diarrheal diseases that affect the population in some municipalities of the semi-arid region of RN from a survey of epidemiological data. For identification of bacteria using commercial kits and the diagnosis of diarrheal disease was based on information from databases. The previous conceptions of teachers and health workers were obtained through questionnaires. The results confirmed the presence of opportunistic bacteria in the studied area, showing the importance of monitoring water quality. There was an under-reporting of cases of diarrhea pointing out flaws in the monitoring of Diarrheal Diseases and indicating the need to improve it. It was felt also the need to implement educational activities on topics dealt with both with teachers and health workers, since they were identified misconceptions on the subject